Locally financed and outside financed regional fiscal multipliers - Pennings, Steven (Elsevier, 2022)
The size of regional fiscal multipliers determines the efficacy of fiscal stimulus, the costs of fiscal austerity and whether countercyclical fiscal policy is more effective at the federal or local level. This paper studies fiscal multipliers in regions of a monetary union—US states, Eurozone members, or countries with a hard exchange-rate peg—and how multipliers are affected by the way spending is financed: local deficit financing, local tax financing or outside financing (federal or foreign aid). I present analytical and quantitative government purchase and transfer multipliers using a New Keynesian model consistent with estimated transfer multipliers in Pennings (2021), focusing on the persistence of the fiscal shock. I find that at business-cycle frequencies, financing has little effect on impact multipliers: outside-financed multipliers are only about 0.07–0.16 larger than local deficit-financed multipliers. This suggests efforts to enable local countercyclical fiscal policy may be a partial substitute for greater fiscal centralization or foreign financing.